Efektivitas Penggunaan Modul Belajar Mata Pelajaran Ekonomi Berbasis Mind Mapping Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X SMA Negeri 3 Tangerang - Syafaatul Hidayati; Badrus Sholeh (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
The purpose of this study in detail to determine the effectiveness of using mind mapping-based economic learning modules in improving students' critical thinking skills. The research method was used by researchers in this research was the quasi research method (Quasi Experiment Research). The test subjects were students of class X IPS at SMA Negeri 3 Tangerang. Data on critical thinking skills were obtained from giving test questions in the form of descriptions. Analysis of critical thinking skills consists of 2 steps, namely the prerequisite test and hypothesis testing. Based on the test results, it showed that the data was normally distributed, with the Shapiro-Wilk pretest sig value 0.069 0.05 and the posttest sig value 0,082 0.05. Moreover, a hypothesis test was carried out to determine differences in critical thinking skills before and after being taught by using a mind mapping based learning module with the Paired Sample T Test statistical technique. The sig value is 0.05 (5%), which means that H0 is accepted, and if the sig value is 0.05 (5%), it means that H0 is rejected. Thus the mind mapping-based economic learning module can improve students' critical thinking skills